Regularity of a Boundary Point for Degenerate Parabolic Equations with Measurable Coefficients - Skrypnik, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the continuity of solutions of quasilinear parabolic equations in the neighborhood of the nonsmooth boundary of a cylindrical domain. As a special case, one can consider the equation \(\frac{{\partial u}}{{\partial t}} - Δ _p u = 0\) with the p-Laplace operator Δp. We prove a sufficient condition for the regularity of a boundary point in terms of C p-capacity.